Risk factors for appendiceal neoplasm and malignancy among patients with acute appendicitis - Brunner, Maximilian; Lapins, Philipp; Langheinrich, Melanie; Baecker, Justus; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Maak, Matthias; Weber, Georg (International Journal of Colorectal Disease, 2019)
Purpose: Non-operative management of acute uncomplicated appendicitis has shown promising results but might carry the risk of delayed diagnosis of premalignant or malignant appendiceal tumors found by chance in 0.7–2.5% of appendiceal specimen after appendectomy. Purpose of this study was to analyze whether appendiceal tumors are associated with a complicated appendicitis and to determine risk factors for appendiceal neoplasm and malignancy in patients with acute appendicitis. Methods: We performed a retrospective analysis of 1033 adult patients, who underwent appendectomy for acute appendicitis from 2010 to 2016 at the University hospital Erlangen. Data included patients’ demographics; comorbidities; pre-, intra- and postoperative findings; and histopathological results. Complicated appendicitis was defined in the presence of perforation or abscess. Results: Appendiceal neoplasm respectively malignancy rate was 2.8% respectively 1.5%. Using univariate analysis, we identified seven risk factors at least for appendiceal neoplasm or malignancy: age, ASA, C-reactive protein, appendiceal diameter, perforation, intraoperative perithyphilitic abscess, and complicated appendicitis. Risk for appendiceal neoplasm or malignancy was 4.4% respectively 2.7% in complicated acute appendicitis compared to 2.0% respectively 1.0% in uncomplicated appendicitis (p = 0.043 respectively p = 0.060). In multivariate analysis, age ≥ 50 years and a diameter of the appendix in the sonography ≥ 13 mm were independent risk factors predicting the presence of appendiceal neoplasm and malignancy. Conclusion: Among patients with appendicitis, there are relevant risk factors predicting appendiceal tumors, especially age and appendiceal diameter in sonography. But the identified risk factors have a low sensitivity and specificity, so obtaining a confident preoperative diagnosis is challenging.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Appendectomy; Appendiceal neoplasm; Complicated appendicitis; Malignancy; Risk factors